Prototype Design and Amenities Clinic Development for Transgender Community - Zakir, Fahad; Imtiaz, Ahsan (Journal of Design and Textiles, 2024)
The current study aimed to survey the health challenges and concerns faced by transgender community and gender-diverse individuals in Pakistan. The term ‘transgender’ refers to a marginalized group of people often denied adequate healthcare facilities due to social stigma and discrimination. Some of these health concerns may occur due to an exposure to gender minority stress. Gender minority stress is related to transgenders seeking precautionary healthcare less often than other people do. By employing a participatory design approach including focus groups and co-design workshops with transgenders and gender-diverse (TGD) community members, this study attempted to identify their specific health needs. In response to these challenges, the project proposed a comprehensive healthcare solution that includes both a specialized healthcare facility and a mobile app. This app would allow transgenders to access health forums, consult with doctors, receive tailored wellness advice, and schedule appointments, making healthcare more accessible and user-friendly for this vulnerable population. This combination of physical and digital healthcare support is designed to improve the overall health and well-being of transgenders in Pakistan.